Financial and Investment Model for Social Security and Sustainable Economic Growth - J. An; A. Yu. Mikhaylov; N. B.A. Yousif (Финансы: теория и практика, 2024)
The subject of the study is the models of social security of the population.   The relevance of the research is derived from the fact that states are increasingly faced with global problems requiring more government funding and restricting how much social risk is covered by state social security mechanisms and models.   The purpose of the study is to form a financial and investment model of social security that promotes sustainable economic growth.   The task is to systematize the aspects of the formation of an optimal financial and investment model of social security. The authors use the methodology of the analysis of the functioning environment (DEA) and the methods of neo-institutionalism, which is the most promising and complete concept for studying structural changes and investment strategies. The main results of the study show that inflation can have a negative impact on the social protection system. An optimal model of social security is proposed to stimulate economic growth. It is concluded that regardless of the division of the social security system into the state and non-state sectors, the proposed model of social security will achieve a synergistic effect and can have a positive impact on the quality and life expectancy of the population, which will favorably affect the indicators of economic activity and economic growth.